9.05.008: "Patrick Boyle interviews Don Walsh for Music 4440, 2 of 2," 23 November 1998 - Boyle, Patrick, 1978- (1998)
Interview for Patrick Boyle, renowned St. John's musician, for his Memorial University Music 4440 course.